From trickster to badman : the Black folk hero in slavery and freedom - Roberts, John W. (John Willie), 1949- (Philadelphia : University of Pennsylvania Press, 1989)
To protect their identity and values, Africans enslaved in America transformed various familiar character types to create folk heroes who offered models of behavior both recognizable to them as African people and adaptable to their situation in America. Roberts specifically examines the Afro-American trickster and the trickster tale tradition, the conjurer as folk hero, the biblical heroic tradition, and the badman as outlaw hero. -- Publisher description from http://www.upenn.edu (Oct. 11, 2011).
Br'er Rabbit and : Trickster heroes in slavery -- The power within: the conjurer as folk hero -- Christian soldiers all: spirituals as heroic expression -- "You done me wrong": the badman as outlaw hero.
Includes bibliographical references (pages 223-229) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
In English.
Keywords: Held, ...; Universidad Sergio Arboleda; African Americans -- Folklore; Folklore -- United States -- History and criticism; Heroes -- United States -- Folklore; Tricksters -- United States; African Americans -- Folklore; Folklore -- United States -- History; Noirs américains -- Folklore; Tricksters -- États-Unis.; Héros -- États-Unis -- Folklore; Noirs américains -- Folklore; Folklore -- États-Unis -- Histoire; Héros -- États-Unis -- Folklore; SOCIAL SCIENCE -- Folklore & Mythology; African Americans; Folklore; Heroes; Tricksters; United States; Geschichte; Schwarze; Volksliteratur; Held; Schwärze; USA; Folklore négro-américain.; African Americans -- Folklore; Folklore -- United States; Heroes -- Folklore -- United States; Tricksters -- United States; Criticism, interpretation, etc; Folklore